Insecticide microemulsion formulation - Omar, Dzolkhifli (2012)

(untitled)
An insecticidal composition includes a formulation. The formulation includes a natural insectidal substance of a plant containing the insectidal substance, a surfactant selected from a group includes an oleochemical surfactant, a nonionic surfactant and combinations thereof and a plant based carrier includes an insectidal oil-containing amide.